(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Background: Newly developed KAtex test can be used as a non invasive tool for diagnosis of Kala-azar. Objectives: The aim of the present study was to validate the KAtex method to diagnose VL. Methodology: This was a cross-sectional study carried out in the Department of Microbiology at Dhaka Medical College, Dhaka, Bangladesh in collaboration with the department of Parasitology at Institute of Epidemiology, Disease control and Research (IEDCR), Dhaka, Bangladesh for a period of one year. Clinically suspected Kala- azar (VL) cases of different age and sex attending IEDCR from different Kala-azar endemic areas of Bangladesh were selected for this study. Microscopy and culture was performed with Bone marrow (BM). KAtex was performed with urine sample. Urine samples taken from cases were pretreated to inactivate heat labile materials which might cause a false positive reaction. Antigen which is detected by KAtex is heat stable carbohydrate antigen. Latex sensitized with antibodies raised against Leishmania donovani antigen was mixed with the urine sample on a glass slide. No agglutination indicates absence of antigen in urine. Result: Cases were 130. Among 130 clinically suspected VL cases, 70 (53.85%) cases were BM positive and 60 (46.15%) cases were BM negative. All the 70 BM positive cases were positive by KAtex. Among 60 BM negative cases, 15 were positive by KAtex. The sensitivity of KAtex is 100% and specificity is 75%. Highest percentage (52.86%) of bone marrow positive cases were below 10 years of age group. Conclusion: In conclusion, KAtex test is a good diagnostic tool for the detection of VL. Bangladesh Journal of Infectious Diseases, December 2017;4(2):45-47